Characteristics of individuals with breast cancer rearrangements in BRCA1 and BRCA2. Issue 10 (12th February 2014) - Jackson, Sarah A.; Davis, Andrew A.; Li, Jun; Yi, Nengjun; McCormick, Shelley R.; Grant, Carly; Fallen, Taya; Crawford, Beth; Loranger, Kate; Litton, Jennifer; Arun, Banu; Vande Wydeven, Kimberly; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Large rearrangements in BRCA1 and BRCA2 occur in a small percentage (< 1%) of patients tested for hereditary breast (BC) and ovarian cancer. It is unclear what factors predict BRACAnalysis Large Rearrangement Test (BART) positivity. METHODS Data from 6 centers were included in this analysis. Individuals with negative Comprehensive BRACAnalysis tested for BART were included. RESULTS From 1300 individuals, 42 (3.2%) were BART positivity. Factors positively associated with BART positivity were Myriad score, first‐degree relatives with BC, infiltrating BC with ductal carcinoma in situ, younger age at BC diagnosis, estrogen receptor–negative BC for both the first and second BC, and Latin American/Caribbean ethnicity. Presence of unilateral BC was inversely associated with BART positivity. Several analyses were performed on the variables available to find the model that best predicts for BART positivity. The BART predictive model, including first BC, ovarian cancer, primary maternal ancestry being Latin America/Caribbean, number of first‐degree relatives with BC of 1 or more versus 0, and family history of prostate and pancreatic cancer, had good predictive ability with an area under the curve of 0.77. CONCLUSIONS Several factors are significantly associated with BART positivity. Among them we have found that Latin American/Caribbean ancestry, Myriad score, first degree relatives with BC, younger age at BC diagnosis, estrogen receptor–negative status of BC, and infiltrating ductal carcinoma with ductal carcinoma in situ features are significantly associated with BART positivity. A BART predictive model may help in a clinical setting. Cancer 2014;120:1557–1564. © 2014 American Cancer Society.